L-fucoside localization in the gills of the genus Takifugu and its possible implication in the parasitism of Heterobothrium okamotoi (Monogenea: Diclidophoridae) - Sato, Yoshiki; Matsunaga, Ryohei; Tasumi, Satoshi; Mizuno, Naoki; Nakane, Motoyuki; Hosoya, Sho; Yamamoto, Atsushi; Nakamura, Osamu; Tsutsui, Shigeyuki; Shiozaki, Kazuhiro; Kikuchi, Kiyoshi (Biochimica et Biophysica Acta (BBA) - General Subjects, 2023)
The monogenean parasite Heterobothrium okamotoi only parasitizes the gills of Takifugu rubripes. In this study, we hypothesized that the carbohydrates contribute to high host specificity of H. okamotoi. T. rubripes, T. niphobles, T. snyderi, and T. pardalis were used for UEA I staining of the gills and an in vivo challenge test against H. okamotoi. To examine the effect of L-fucose, an in vitro detachment test was conducted using the host's gills. Additionally, fucosylated proteins were isolated from the membrane proteins of T. niphobles gills. The location of L-fucoside and the infection dynamics in four species were correlated to some extent; H. okamotoi detached relatively quickly from T. niphobles possessing L-fucoside both on the surface of the gills and in certain types of cells, including mucus cells, but detached slowly from T. snyderi possessing L-fucoside in only certain types of cells, including mucus cells. Under the conditions examined, H. okamotoi exhibited minimal detachment from T. rubripes and T. pardalis, and L-fucoside was not detected. The significantly higher detachment rate of H. okamotoi from the host's gills incubated in L-fucose-containing medium compared with the controls suggests that L-fucose in the non-host gills induced detachment of H. okamotoi. Four fucosylated proteins, including mucin5AC-like, were identified as potential factors for the detachment of H. okamotoi. Fucosylated proteins covering the surface of non-host gills might contribute to H. okamotoi detachment. This research shows the possible involvement of oligosaccharides in the host specificity of monogenean parasites. [Display omitted] •L-fucoside localization pattern on the gills was different among the species of genus Takifugu.•L-fucose has ability to induce H. okamotoi detachment from its hosts' gills in vitro.•A species of nonhost, that can detach H. okamotoi from its gills within a week, possessed L-fucoside on its gill surface and in gill mucus as fucosylated Mucin5ac-like protein.•There was a positive correlation between L-fucoside localization pattern and H. okamotoi parasitization dynamics.•Host recognition mechanism via carbohydrate-protein interaction could be utilized in wide combination of fish and their monogenean parasites.